The last century of symptom-oriented research in emergency presentations – have we made any progress? (Swiss Medical Weekly, 2013)
This review is dedicated to the last century of symptom-oriented research, taking three symptom complexes as typical examples of medical progress, and focusing on emergency presentations. Landmark publications in each area are discussed, with an attempt to focus on the methods used to achieve major breakthroughs. In abdominal pain, progress was achieved over a century ago by correlating symptoms and surgical pathology. Most diagnoses were made by using the clinical tools elaborated with careful observation and clinical examination. Together with the later reported outcomes, surgeons had an early and powerful tool for symptom-oriented research. In dyspnoea, progress was achieved much later, as a universal definition had to be elaborated over decades by consolidating clinical research, predominantly symptom-pathology correlation, and experimental research, such as function testing and experiments with animals and humans. In nonspecific presentations in emergency situations, progress has been achieved only recently, most probably owing to the fact that elderly patients are presenting in steeply increasing numbers, and the hallmark of disease presentation in the elderly seems to be less specific symptoms and complaints. This may be caused by altered physiology, polymorbidity, polypharmacy and the multiple difficulties encountered when taking histories in the elderly. Taken together, symptom-oriented research has been an important contributor to medical progress in the last century. Though it may be challenged by image- and laboratory-oriented research, it will remain part of patient-centred research because the epidemiology of symptoms, their clinical outcomes and their diagnostic importance according to severity will be the basis for the diagnostic process.   Key words: nonspecific disease presentation, symptom-oriented research, dyspnea, abdominal pain, elderly, geriatric emergency